Sensitivity and specificity of in situ proximity ligation for protein interaction analysis in a model of steatohepatitis with Mallory-Denk bodies. - Bernhard Zatloukal; Iris Kufferath; Andrea Thueringer; Ulf Landegren; Kurt Zatloukal; Johannes Haybaeck (PLoS ONE)
The in situ proximity ligation assay (isPLA) is an increasingly used technology for in situ detection of protein interactions, post-translational modifications, and spatial relationships of antigens in cells and tissues, in general. In order to test its performance we compared isPLA with immunofluorescence microscopy by analyzing protein interactions in cytoplasmic protein aggregates, so-called Mallory Denk bodies (MDBs). These structures represent protein inclusions in hepatocytes typically found in human steatohepatitis and they can be generated in mice by feeding of 3,5-diethoxy-carbonyl-1,4-dihydrocollidine (DDC). We investigated the colocalization of all three key MDB components, namely keratin 8 (K8), keratin 18 (K18), and p62 (sequestosome 1) by isPLA and immunofluorescence microscopy. Sensitivity and specificity of isPLA was assessed by using Krt8-/- and Krt18-/- mice as biological controls, along with a series of technical controls. isPLA signal visualization is a robust technology with excellent sensitivity and specificity. The biological relevance of signals generated critically depends on the performance of antibodies used, which requires careful testing of antibodies like in immunofluorescence microscopy. There is a clear advantage of isPLA in visualizing protein co-localization, particularly when antigens are present at markedly different concentrations. Furthermore, isPLA is superior to confocal microscopy with respect to spatial resolution of colocalizing antigens. Disadvantages compared to immunofluorescence are increased costs and longer duration of the laboratory protocol.